(untitled) (Conferencea, 2023)
Formative assessment provides numerous benefits that enhance student learning, such as targeted feedback, clear learning expectations, active engagement, error correction and learning gap identification, scaffolded learning, and metacognitive development. By incorporating formative assessment into instructional practices, educators can create a dynamic and supportive learning environment that optimizes student learning outcomes. This article discusses the ways in which formative assessment contributes to enhancing student learning and provides a summary of its benefits.